Ентропійні параметри соціально-економічної пружності регіонів - Бурлуцька, C. В.; Burlutska, S. (КНТУ, 2015)
У статті розглянуті питання оцінки ентропійних параметрів соціально-економічної пружності регіонів. Проведено кластерний аналіз за параметром структурної ентропії (за видами економічної діяльності) та глибиною шоку (падіння валового регіонального продукту) за 2013-2014 роки). Визначені регіональні особливості пружної реакції на шокові збурення. Емпірично підтверджено прояв ефектів модульності, структурної нейтральності, міжрегіональної субституційності та компліментарності. Наведені пропозиції щодо покращення інформаційної вірогідності ентропійних параметрів соціально-економічної пружності. The events of the past two years illustrate the most significant shock effect on the domestic socio-economic system. In this context deepening of territorial imbalances necessitated the development of differentiated approaches to formation of strategy and tactics for regional development. The solution of this problem is impossible without a perfect research of reaction features of regional systems on recessionary symptoms. The purpose of this investigation is the definition of entropy characteristics of the region socio-economic resilience as a response to shock disturbances of Ukrainian economy in 2013-2014. Socio-economic resilience is the ability of an economy (region) to withstand or recover from market, competitive, environmental, and other external shocks and to return to the path of growth. The economic structure of a region (structure existing activities) affects the exposure and vulnerability to different types of shock, and determines the robustness of local socio-economic system etc.
Entropy Parameters of Socio-Economic Resilience of Regions
Keywords: регіон; соціально-економічна пружність; модульність; структурна нейтральність; компліментарність; субституційність; region; socio-economic resilience; modularity; structural neutrality; complementarity; substituting